Nonalcoholic fatty liver disease in the over-60s: Impact of sarcopenia and obesity - Karn Wijarnpreecha (2019)
© 2019 Elsevier B.V. Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in children and adults of all ethnicities. NAFLD is commonly seen in individuals with metabolic abnormalities, such as obesity and insulin resistance, which are closely associated with sarcopenia. Sarcopenia, defined as low muscle mass and impaired muscle function, is associated with NAFLD and worse outcomes in patients with NAFLD. As the world's elderly population and the prevalence of obesity continues to grow at an unprecedented rate, NAFLD and sarcopenia are projected to increase. Given that there are no approved pharmacologic treatments for NAFLD, it is imperative to gain a better understanding of the disease pathophysiology, to guide treatment options. Recent studies have given new insight into sarcopenic obesity, but there is no consensus on its definition. In this review, we attempt to address the impact of sarcopenia and obesity on NAFLD, especially in the elderly population.